The Mixing of Passive and Non-Passive Resultative Adjectives in Polish - Cetnarowska, Bożena (Lingua Posnaniensis, 2013)
The present paper aims to investigate the class of Polish resultative adjectives. Section 1 gives a brief overview of participial adjectives in Polish, referred to as “resultatives” in studies on Polish wordformation. Sections 2 and 3 examine the ambiguity between perfect and resultative interpretation of participial adjectives, as well as the distinction between subject-oriented and object-oriented adjectives. The discussion in sections 4-6 focuses on the rivalry between two adjectivizing suffixes in Polish: the suffix -ł- (which also appears in past tense forms) and the suffix -n-/-t- (which functions as a passive marker). Special attention is paid to the occurrence of novel nonstandard S-oriented resultative adjectives terminating in -nięty, such as wyblaknięty (colloq.) ‘faded’.